The Pacific flyway - Waterfowl in the Pacific flyway of North America - Marshall, David B (Wildfowl, 1957)
The Pacific flyway encompasses approximately the western quarter of North America. Between its breeding grounds and wintering areas pass some 10 million swans, geese and ducks each year. In the United States portion of the flyway these birds are hunted by about 450,000 sportsmen and are enjoyed by countless others. The Pacific flyway is one of four flyways recognised in North America. Although many birds pass from one to another, the flyway boundaries generally follow mountain ranges or other geographical features restricting movement between flyways. Waterfowl surveys, research, hunting regulations and other matters pertaining to this resource are carried out on a flyway basis. This article, using the Pacific flyway as an example, illustrates the activities being carried out with regard to waterfowl in the United States. Mention is also made of the main species of the Pacific flyway and their migration patterns.